Provisional Agenda for the Twenty-Ninth Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper, 2014)
The following is the provisional agenda for the Twenty-Ninth Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on April 11, 2014.